Synchronization of Notary Supervision by Notary Supervision Assembly in Law Enforcement - Suwardi Suwardi (Sultan Agung Notary Law Review, 2021)
The Notary Institution, one of the social institutions in Indonesia, arises from the need in human relations that requires a means of evidence regarding the civil law relationship that exists and or occurs between them. The authority of a notary is regulated in Article 1 number 1 of Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Position of a Notary (hereinafter abbreviated as UUJN) which states that: "Notary is a public official who is authorized to make authentic deeds and has other powers as referred to in this Law or based on other laws." In line with the Notary's accountability for his authority, and compliance with that authority, legal certainty must be guaranteed with a continuous and effective supervision and guidance. There are currently two notary supervision and guidance institutions in Indonesia, namely the Notary Supervisory Council and the Notary Honorary Council.